Mitral Valve Echodensities in a Young-Adult Female with Relapsing Polychondritis, Transiently Positive Lupus Anticoagulant, and Systemic Embolism - Michael C. Sauer; Vikram Sharma; Jennifer L. M. Strouse; Ramzi El Accaoui; Christopher J. Benson (Case Reports in Cardiology)
Background. Valvular strands seen on echocardiography carry a wide differential diagnosis and may not always have a clear etiology despite taking clinical context into account. The decision of whether to provide anticoagulation for these lesions can be challenging. Case Presentation. A young adult female with an extensive rheumatologic history involving relapsing polychondritis and positive lupus anticoagulant presents to the emergency department with a discolored and painful right toe, as well as right auricular pain and swelling. Initial work-up revealed a possible splenic infarct, vasculitis of the right lower extremity, and mitral valve echodensities on echocardiography, without evidence of infective endocarditis. Due to concern that nonbacterial thrombotic endocarditis may be the cause of the patient’s thromboembolic event, her valvular lesions were treated with low molecular weight heparin while awaiting serial imaging. When follow-up echocardiography showed no change in the size of her mitral valve lesions, which would be most consistent with Lambl’s excrescences, the care team still faced a decision about which long-term anticoagulation to prescribe. This patient of childbearing age wished to avoid the teratogenicity and long-term monitoring associated with warfarin therapy. Although warfarin was the preferred agent for the patient’s rheumatologic comorbidities, she elected to receive enoxaparin therapy for long-term thromboembolism prophylaxis. Conclusions. Even when accounting for clinical context, valvular lesions seen on echocardiography often have uncertain etiology and may require time and serial imaging to determine which treatment to pursue. When long-term anticoagulation is provided for females of childbearing age, shared decision-making with consideration of the patient’s personal priorities and comorbidities is essential.